Self-efficacy and work readiness among vocational high school students - Fatwa Tentama; Netty Merdiaty; Subardjo Subardjo (Journal of Education and Learning (EduLearn), 2019)
This study aims to empirically examine the effect of self-efficacy on students' work readiness. The subjects in this study were students of class XII of State Vocational High School 1 Seyegan totalling 174 students which were obtained by cluster random sampling. The research method used is a quantitative method with work readiness scale and self-efficacy scale. Analysis of the data used in this study is a simple regression analysis technique. The results of data analysis showed a very significant effect of self-efficacy on work readiness, with the F test, namely: 22.768, with a significance level (p) of 0.000 (p less than 0.01). The contribution of the effect of self-efficacy of 11.2% on work readiness and the remaining 88.8% was influenced by other factors outside the variables studied. It means that students’ self-efficacy can predict their work readiness.